NEW DATA ON THREE SPECIES OF KOELLIKERIOIDES (DIGENEA, DIDYMOZOIDAE) IN BRAZILIAN TUNA FISHHOPKINSI (EUCESTODA, HYMENOLEPIDIDAE) IN NETTA PEPOSACA (AVES, ANATIDAE) IN SOUTH AMERICA - Nascimento Justo, Márcia Cristina (2011)
Four species of scombrid fishes (Perciformes) from the coastal zone of Rio de Janeiro, Brazil, wereexamined for helminth parasites. These are Thunnus albacares (Bonnaterre, 1788), Thunnus atlanticus(Lesson, 1831), Thunnus obesus (Lowe, 1839) and Euthynnus alletteratus (Rafinesque, 1810). Threespecies of the genus Koellikerioides Yamaguti, 1970: K. apicalis Yamaguti, 1970, K. externogastricusYamaguti, 1970 and K. intestinalis Yamaguti, 1970, were recorded from the gill raker, the outer musclelayer of the stomach wall and the inner surface of the small intestine, respectively. Originalmeasurements, parameters of infection and original figures are presented. K. apicalis and K. intestinalisshowed the typical aggregated distribution pattern. Statistical analysis showed that there was asignificant negative correlation between the total lengths of E. alletteratus and the prevalence of K.intestinalis. The findings of K. apicalis in T. atlanticus and of K. intestinalis in T. atlanticus and E.alletteratus represent new host records. All species are reported for the first time in the SouthwestAtlantic Ocean.